Effects of arsenic and its interaction with phosphorus on yield and arsenic accumulation in rice (Journal of the Bangladesh Agricultural University, 2010)
A study was made on the effect of arsenic (As) and As X P interaction in Boro rice and its residual effect in succeeding T. Aman rice. Arsenic was added to soil (having 2.6 ppm initial As) @ 0, 15 and 30 mg As kg -1 from Na2HAsO4.7H2O and phosphorus @ 0, 20, 40, 60 and 80 mg P kg-1 from KH2PO4. Each pot had received 100 ppm N, 40 ppm K and 25 ppm S from urea, MoP and gypsum, respectively. The grain yield of Boro rice was reduced by 20.6 % for 15 ppm As treatment and 63.8 % due to 30 ppm As. Such reductions for straw yield were 21.0 and 65.2 % with these two As treatments, respectively. Residual effect of arsenic was also significant and negative in T. Aman rice. The grain-As concentration in all cases was below 1 ppm, and the straw-As content was well above 1 ppm. The arsenic concentrations of both grain and straw were lower in T. Aman rice than in Boro rice. The adverse effect of arsenic was further enhanced by P addition. This reaction has an implication to P fertilizer management in rice.Keywords: Arsenic; Phosphorus; RiceDOI: 10.3329/jbau.v6i2.4822 J. Bangladesh Agril. Univ. 6(2): 277-284, 2008